2021
DOI: 10.3390/ijerph18094873
|View full text |Cite
|
Sign up to set email alerts
|

Reshoring Decisions for Adjusting Supply Chains in a Changing World: A Case Study from the Apparel Industry

Abstract: Global conditions for manufacturing are evolving rapidly and the myopic financial factors that once made overseas locations attractive for offshoring are now in favor of revising it. Besides, the COVID-19 pandemic has highlighted the need for restoring the previously offshored competencies. As a strategic decision, reshoring requires a balance of short- and long-term financial and non-financial considerations. This study extends the reshoring literature by exploring the underpinnings of the decision. For this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…As already underlined, Bettiol et al (2019) found that apparently contradictory location strategies can coexist within the same firm, namely back-shoring and further offshoring; in this respect, our first contribution is regarding the decision-making issues that induce companies to simultaneously implement such post-offshoring strategies, supporting the studies that underline the complexity of offshoring and post-offshoring strategies and the need for a multi-strategic approach (e.g. Pourhejazy and Ashby, 2021). Evidence shows that firms prefer further offshoring in low-cost countries when they need to scale production, but back-shore when they need to increase the perceived value of their products.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…As already underlined, Bettiol et al (2019) found that apparently contradictory location strategies can coexist within the same firm, namely back-shoring and further offshoring; in this respect, our first contribution is regarding the decision-making issues that induce companies to simultaneously implement such post-offshoring strategies, supporting the studies that underline the complexity of offshoring and post-offshoring strategies and the need for a multi-strategic approach (e.g. Pourhejazy and Ashby, 2021). Evidence shows that firms prefer further offshoring in low-cost countries when they need to scale production, but back-shore when they need to increase the perceived value of their products.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, the evidence based on the analyses of the case studies of companies reconsidering their offshoring decisions can contribute to identifying possible strategies and decisions in the post-pandemic context. In fact, both academics and practitioners debate the organization of GVCs after the COVID-19 shock, identifying various potential trajectories (Barbieri et al, 2020a, b;Juergensen et al, 2020;McIvor and Bals, 2021;Miroudot, 2020;Pourhejazy and Ashby, 2021;Strange, 2020;Verbeke, 2020;UNCTAD, 2020b). Our study highlights the factors that drive decisions regarding post-offshoring strategies, supporting companies' decision-making in the new global scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, two main research streams shape the literature's structuring of reshoring. First, adopting a supply or firm perspective, studies identify important firm-based drivers such as economic advantages (Bailey and De Propris, 2014) or unique competencies (Pourhejazy and Ashby, 2021). The second and more recent research stream (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, many small- and medium-size organizations have been forced to close down or limit their operations, causing job losses. To overcome the impact of disruptions caused by the major disruptive events, like pandemics, organizations need to be more supportive of local companies and products, while organizations need to source more products and raw materials from local suppliers and small businesses, which in turn improves employment opportunities for locals [7] , [66] .…”
Section: Discussionmentioning
confidence: 99%